Valvular pulmonary stenosis: preoperative and postoperative studies - Tuncali, Tahsin; Saraçlar, Muhsin (The Turkish Journal of Pediatrics, 1964)
Preoperative and postoperative physical observations, electrocardiograms, phonocardiograms and x-rays of patients with pulmonary stenosis are discussed. The relationship between the R waves in V1 and right ventricular pressure is examined. The following observations are presented: 1. After valvotomy, the intensity of the murmur decreased in all cases. In some, however, a low-frequency residual murmur remained, probably because of residual poststenotic dilatation. 2. Thrill disappeared in all cases. 3. Poststenotic dilatation disappeared completely in two young patients, suggesting that the operation should be performed while the pulmonary artery is still elastic. 4. The ratio between the right ventricular pressure and the length of the R wave in V1, where strain is absent, is 4. 5. There is a direct relation between the fall in right ventricular pressure and the decrease in RV1, in the electrocardiogram during the first four months following valvotomy.